Achievement of the Selectivity of Cytotoxic Agents against Cancer Cells by Creation of Combined Formulation with Terpenoid Adjuvants as Prospects to Overcome Multidrug Resistance - Zlotnikov, Igor D.; Dobryakova, Natalia V.; Ezhov, Alexander A.; Kudryashova, Elena V. (International journal of molecular sciences, 2023)
Oncological diseases are difficult to treat even with strong drugs due to development the multidrug resistance (MDR) of cancer cells. A strategy is proposed to increase the efficiency and selectivity of cytotoxic agents against cancer cells to engage the differences in the morphology and microenvironment of tumor and healthy cells, including the pH, membrane permeability, and ion channels. Using this approach, we managed to develop enhanced formulations of cytotoxic agents with adjuvants (which are known as efflux inhibitors and as ion channel inhibitors in tumors)—with increased permeability in A549 and a protective effect on healthy HEK293T cells. The composition of the formulation is as follows: cytotoxic agents (doxorubicin (Dox), paclitaxel (Pac), cisplatin) + adjuvants (allylbenzenes and terpenoids) in the form of inclusion complexes with β–cyclodextrin. Modified cyclodextrins make it possible to obtain soluble forms of pure substances of the allylbenzene and terpenoid series and increase the solubility of cytotoxic agents. A comprehensive approach based on three methods for studying the interaction of drugs with cells is proposed: MTT test—quantitative identification of surviving cells; FTIR spectroscopy—providing information on the molecular mechanisms inaccessible to study by any other methods (including binding to DNA, surface proteins, or lipid membrane); confocal microscopy for the visualization of observed effects of Dox accumulation in cancer or healthy cells depending on the drug formulation as a direct control of the correctness of interpretation of the results obtained by the two other methods. We found that eugenol (EG) and apiol increase the intracellular concentration of cytostatic in A549 cells by 2–4 times and maintain it for a long time. However, an important aspect is the selectivity of the enhancing effect of adjuvants on tumor cells in relation to healthy ones. Therefore, the authors focused on adjuvant’s effect on the control healthy cells (HEK293T): EG and apiol demonstrate “protective” properties from cytostatic penetration by reducing intracellular concentrations by about 2–3 times. Thus, a combined formulation of cytostatic drugs has been found, showing promise in the aspects of improving the efficiency and selectivity of antitumor drugs; thereby, one of the perspective directions for overcoming MDR is suggested.